Synthesis and biological evaluation of novel PqsR antagonists to combat Pseudomonas aeruginosa infections - Mashabi, Alaa (2021)
Pseudomonas aeruginosa is an important opportunistic pathogen that belongs to superbug microorganisms and shows an increased number of multi-drug resistant (MDR) clinical isolates. P. aeruginosa has three hierarchically organised quorum sensing (QS) or cell to cell communication systems named las, rhl and pqs. The las and rhl are classic QS systems that use an N‐(3‐oxododecanoyl) ‐L‐homoserine lactone as autoinducers. The las system is the major QS system of the cell and controls the other two and there is partial redundancy with the rhl system regarding the genes and functions controlled by the system. The pqs quorum sensing system of P. aeruginosa is a major regulatory network that controls the expression of genes involved in virulence, biofilms, oxidative stress and iron acquisition, especially in chronic conditions. The transcriptional regulator of the pqs system is PqsR which becomes functional upon direct binding to the main autoinducer of the receptor, PQS and its precursor HHQ. The inhibition of QS and in particular the pqs system is an approach to decrease the virulence of P. aeruginosa in vivo, improve the outcome of antibiotic treatments and decrease the P. aeruginosa associated morbidity. This work aims to develop PqsR antagonists that attenuating the pathogenicity and resistance of one of the most critical pathogens by designing and developing a range of novel QS inhibitors targeting the transcriptional regulator (PqsR) of the pqs system which is distinct to P. aeruginosa. Different chemical approaches are employed to synthesise a range of compounds, and the selected candidates are validated through different biological evaluations and molecular structure analysis. Chapter 2 focuses mainly on a SAR study for the selected hit, founded by in silico screening, with a quinazolin-4(3H)-one scaffold which is similar to the natural substrate of the receptor. In Chapter 3, the work aimed to expand the SAR further by replacing the quinazolin 4(3H)-one moiety with different heterocyclic ring systems; it was concluded that the optimal replacement is the 1-methyl-1H-benzo[d]imidazol-2-amine ring. Many attempts were established to identify the optimal conditions to synthesise this series by employing different strategies, and the selected pathway was successful in synthesising a range of analogues with good yield. Cell based reporter gene assay with PAO1-L CTX::PpqsA-lux strain of P. aeruginosa was employed to evaluate the activity of the compounds. Furthermore, the active compounds with sub-micromolar potency were analysed in pyocyanin quantification assay. 3.20 was analysed further in alkyl quinoline quantification assay against different genomic classes of P. aeruginosa. The crystal structures of PqsRCBD complexed with key compounds presented in chapter 2 and 3 were attained. These biological evaluations are presented in this work in an attempt to prove the concept and validate PqsR as a relevant therapeutic target. Furthermore, a cytotoxicity study of the most active compounds in the series was conducted to investigate the therapeutic-toxicity index of these compounds before proceeding to the in vivo study. Overall, this project has led to the successful development of hit to lead optimization study starting with previously identified compound 2-(4-(3-(6-chloro-4-oxoquinazolin-3(4H)-yl)-2 hydroxypropoxy) phenyl) acetonitrile, 1.6 (IC50= 3.2 µM in PAO1-L) leading to a new series of potent benzimidazole containing compounds. 2-(4-(3-((6-chloro-1-isopropyl-1H benzo[d]imidazol-2-yl) amino)-2-hydroxypropoxy) phenyl) acetonitrile 3.20 (PAO1-L IC50 0.13 ± 0.04 µM, PA14 IC50 0.09 ± 0.01 µM) is one of the most potent PqsR antagonists in this series with high potency inhibition of pqs system signalling. In addition, 3.20 showed wide spectrum efficacy against different genomic classes of P. aeruginosa with significant inhibition of P. aeruginosa pyocyanin and AQ production. The co-crystal structure of 3.20 and some analogues with PqsRLBD were determined which revealed specific binding interactions of this new class of inhibitors. In addition, cytotoxicity studies revealed that 3.20 had a good safety margin against a human cell line which support 3.20 progression to a murine in vivo study. However, it is critical to establish further pharmacokinetics in vitro and in vivo assays as well as a biofilm formation model to evaluate the efficacy or safety of the novel candidate which are beyond the scope of this thesis.